Categorization of Diabetic Retinopathy Severity Levels of transformed images using clustering approach. - Nair, Manjusha; Mishra, Dhirendra S (International Journal of Computer Sciences and Engineering, 2019)
Diabetic Retinopathy is a diabetic complication that affects the eyes and can lead to blindness. The main cause of this condition is the damage to the blood vessels of the light sensitive tissue at the back of the retina. This paper attempts to categorize diabetic retinopathy with its various severity levels using clustering approach. Different Transforms such as WalshHadamard, DCT and DST have been applied to the pre-processed image to extract the features of the image. These extracted features are used for Clustering of those images. The algorithmic performances are measured subjectively and objectively. The normal images were very well classified and distinguishable from the database using the proposed approach.